An Empirical Study on Social Media as a New World for Talent Acquisition a Factor Analysis Approach - Zionia.A, Esther; J, Sathyapriya (International Journal of Engineering and Technology, 2018)
In this digital age, technology become mandatory as it connects everyone around the world. Improvement of technology became revolutionised in the exchange of information. After the invention of blogging, social media began to be popular. One of the best ways to communicate with the people is social media. Six Degrees was the first recognizable social media site which was founded in the year 1997. Now there are many social media sites such as linkedIn, Facebook, Twitter, Instagram, Google+ and others. Rather than, social media has come up with a new idea of recruiting candidates for the organisation. AcquiringÂ talented candidates in person became a difficult task due to insufficient time and more expensive. To save time and cost, technology is used in this digital era. Now-a-days social media helps to acquire talented people for organisation. It became quite popular among head-hunters. Social media has became modern, easy and inexpensive to approach the prospects. Social media helps to identify potential job candidates in other) geographic regions. Head-hunters can acquire a talented person from all over the world because of this revolution in technology. The descriptive study is to identify the most used social media site for talent acquisition and impact of social media on talent acquisition. 126 employers of IT/ITES companies from Chennai city were selected using convenience sampling to identify the factors influencing the use of social media in talent acquisition.Â